Gangguan Kepribadian Akibat Kecanduan Bermain Game Pada Gamers - Wiriansya, Edward Pandu; Noor, Andi Muhammad Reza Cesaria; Rahman, Titin Suhartina; Abdi, Dian Amelia; Ratu, Andi Puspa (Window of Health : Jurnal Kesehatan, 2020)
Electronic games or often referred to as online games, have experienced very rapid development and progress. This can be seen in various small cities in all corners of Indonesia, where many game centers have emerged. Even lately, the type and theme of the game that develops leads to the theme of violence that triggers aggressive behavior in adolescents. In addition, as the number of game addicts increases, the number of criminal acts triggered by the game increases. The purpose of this study was to determine the relationship of addiction to playing games with personality disorders in game players. This research uses observational analytic method with cross sectional design. The research subjects were game players in the Makassar City Game Center which were taken in total sampling. Data is collected using Game Addiction Scale (GAS) questionnaire, Mini International Neurophysciatric Interview (MINI), and game player data sheets. Hypothesis testing the correlation between addiction to playing games with personality disorders was analyzed by the two free sample T Test. Of the 50 gamers in the Game center that were sampled, there were 48 people who experienced personality disorders. Bivariate analysis of addiction to play games associated with personality disorders obtained p value = 0,000, the type of game not related to personality disorders obtained p value = 0.745, and the duration of playing games related to personality disorders obtained p value = 0.001. The conclusion is that there is a relationship between addiction and the duration of playing games with personality disorders. It is recommended not to always use the game so that it does not experience personality disorders.